Factors determining the usage of open access journals in Agricultural Research Institutes in Tanzania - Massoro, Zainabu Zuberi (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
The study of the factors that determine the Open Access Journals (OAJs) usage behaviour is very important in order to enhance provision of quality services by information professionals, researchers and public at large. OAJs form a virtual platform for knowledge sharing, free accessibility and dissemination of research findings. Through OAJs publishing, the public funds spent on research can bring about changes to the society, such as having a knowledge-based society, building institution and individual reputation, and enhancing the visibility of publications. However, there has been underutilization of OAJs despite the diverse OAJs platforms. Since its inception, studies on the usage of OAJs have been reported a handful usage in most African countries and Tanzania in particular. Consequently, the factors that influence the usage of OAJs among individuals have received less attention. This research addresses the factors determining OAJs usage behaviour in a non-university institution, specifically the Agricultural Research Institutes (ARIs) in Tanzania. The research adapted the Ajzen and Fishbein's (1980) Theory of Reasoned Action (TRA) as the theoretical framework. The research adopted a mixed methods approach, thereby using both quantitative and qualitative research designs for collecting and analyzing the data. The quantitative data were collected using self-administered questionnaires while the qualitative data was gathered via in-depth interview. The quantitative data were collected from 281 researchers in four ARIs from four zones and were analyzed using Statistical Package for Social Science (SPSS) version 23.0 and SmartPLS 2.0 M3 software. The qualitative data was gathered via interview with 10 participants, from 4 ARIs in four Tanzania agricultural zones. The quantitative analysis process involved assessment of the measurement model to evaluate its reliability and validity, followed by the assessment of the structural model and hypotheses testing. The results of the quantitative analysis were complemented with the qualitative data analysis. The findings revealed that OAJs usage behaviour is significantly influenced by intention. Meanwhile, intention is also significantly influenced by attitude, subjective norm and content respectability. Similarly, the results indicated that attitude is positively influenced by personal innovativeness and IT infrastructure, while subjective norm was found to be significantly positively influenced by management support. The result indicates that OAJs usage behaviour to a great extent is influenced by awareness and intention, while predatory journals negatively influence OAJs usage behaviour among researchers. Further, the analysis of mediation effect showed that intention fully mediates between attitude and subjective norm, and it also partially mediates between content respectability and OAJs usage behaviour. Recommendations based on these findings were made. This research sheds light on the applicability of the Theory of Reasoned Action in determining factors that influence the OAJs usage behaviour. It also fills in the gap in literature on OAJs usage behaviour, particularly in Agricultural Research Institutions.